2022
DOI: 10.3390/atmos13111769
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Spatio-Temporal Rainfall Variability in Cameroon over the Period 1950 to 2019

Abstract: The study of rainfall in the long term is essential for climatic change understanding and socioeconomic development. The main goal of this study was to explore the spatial and temporal variations of precipitation in different time scales (seasonal and annual) in Cameroon. The Mann–Kendall and Pettitt tests were applied to analyze the precipitation variability. In temporal terms, the different regions of Cameroon have recorded significant drops in annual rainfall that Pettitt’s test generally situates around th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Using a the arithmetic mean of three different precipitation products, our analyses show, respectively, increasing and decreasing trends in annual precipitation in the southern and northern parts of the GGB. Annual precipitation decline in the northern part of the GGB is consistent with results from other studies in the region using precipitation estimates from CHIRPS (Bichet & Diedhiou, 2018; Nkiaka, 2022) and Climate Research Unit (Ebodé, 2022). Rainfall decline in Central Equatorial Africa has been attributed partly to sea surface temperature variations over the Indo‐Pacific linked with the enhanced and westward extended tropical Walker circulation (Hua et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…Using a the arithmetic mean of three different precipitation products, our analyses show, respectively, increasing and decreasing trends in annual precipitation in the southern and northern parts of the GGB. Annual precipitation decline in the northern part of the GGB is consistent with results from other studies in the region using precipitation estimates from CHIRPS (Bichet & Diedhiou, 2018; Nkiaka, 2022) and Climate Research Unit (Ebodé, 2022). Rainfall decline in Central Equatorial Africa has been attributed partly to sea surface temperature variations over the Indo‐Pacific linked with the enhanced and westward extended tropical Walker circulation (Hua et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…This allowed us to make much more precise supervised classi cations (close to reality). Their formulas are as follows (Ebodé, 2022):…”
Section: Discussionmentioning
confidence: 99%
“…This is data from the National Centers for Environmental Prediction (NCEP). It has been shown that these data could constitute a good alternative for rainfall study and modelling ows in ungauged regions (Nkiaka et al, 2017;Ebodé, 2022c). All the meteorological data used were collected over the period 1998-2008.…”
Section: Datamentioning
confidence: 99%